2021
DOI: 10.3390/ijerph18063069
|View full text |Cite
|
Sign up to set email alerts
|

Distance Motor Learning during the COVID-19 Induced Confinement: Video Feedback with a Pedagogical Activity Improves the Snatch Technique in Young Athletes

Abstract: The purpose of the present study was to investigate which of two strategies, Video Feedback with Pedagogical Activity (VF-PA) or Video Feedback (VF), would be more beneficial for the remote error correction of the snatch weightlifting technique during the confinement period. Thirty-five school aged children with at least three months of weightlifting experience were randomized to one of three training conditions: VF-PA, VF or the Control group (CONT). Subjects underwent test sessions one week before (T0) and o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 47 publications
(68 reference statements)
0
14
0
Order By: Relevance
“…Meanwhile, in other countries, advanced technologies were already in use, including video feedback with activity or pedagogical control, which allowed for the establishment of ways of technical training and adjustment for the disadvantages caused by online education. [8].…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, in other countries, advanced technologies were already in use, including video feedback with activity or pedagogical control, which allowed for the establishment of ways of technical training and adjustment for the disadvantages caused by online education. [8].…”
Section: Introductionmentioning
confidence: 99%
“…Innovative knowledge and skill delivery models have been suggested to engage athletes and PE students through varying degrees of technology-mediated active learning formats and, thus, partially abandoning the conventional “passive” model where the teacher or coach is the transmitter of information, and the student or athlete is a passive receiver. 12 The use of technology-mediated active learning methods has become common in sport and exercise pedagogy. Indeed, the active participation of the learner in the learning process improves performance compared to the traditional one-way knowledge transmission model where content is passively delivered to learners.…”
Section: Introductionmentioning
confidence: 99%
“…Different studies have applied digital technologies to promote distance-education before COVID-19 pandemic with promising results. Besides, recent studies have showed positive psychosocial effects of the use of communication technologies during home teaching and during home physical training during home confinement ( Souissi et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%